2019
DOI: 10.1097/01.nep.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Adelante (Moving Forward): An Innovative Program for Nursing and Prenursing Students

Abstract: The US population reflects a rich diversity of people that is not reflected in the health care workforce. This article describes the Adelante (Moving Forward) Program, an innovative model designed to increase nursing workforce diversity. Adelante was created to advance baccalaureate nursing students and prenursing students by using supportive developmental relationships and mentoring strategies. Graduates stated that they planned to advance their education. Further development of innovative programs for nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…9 Publications described strategies to increase the diversity of students in undergraduate nursing programs, focusing on recruitment, faculty engagement, and mentorship. [10][11][12][13][14] Others emphasized the need for emotional, financial, and academic support to allow students to thrive. 15,16 However, no publications were identified that focused on how to increase the diversity of nurses in clinical practice settings.…”
Section: Increasing Diversity Of the Nursing Workforcementioning
confidence: 99%
See 1 more Smart Citation
“…9 Publications described strategies to increase the diversity of students in undergraduate nursing programs, focusing on recruitment, faculty engagement, and mentorship. [10][11][12][13][14] Others emphasized the need for emotional, financial, and academic support to allow students to thrive. 15,16 However, no publications were identified that focused on how to increase the diversity of nurses in clinical practice settings.…”
Section: Increasing Diversity Of the Nursing Workforcementioning
confidence: 99%
“…Publications described strategies to increase the diversity of students in undergraduate nursing programs, focusing on recruitment, faculty engagement, and mentorship 10-14 . Others emphasized the need for emotional, financial, and academic support to allow students to thrive 15,16 .…”
Section: Increasing Diversity Of the Nursing Workforcementioning
confidence: 99%